Holistic Approach of Eleocarpus Ganitrus (Rudraksha) in Hypertension and Neurological Disorders -A Review. - Yadav, Manju (International Research Journal of Ayurveda & Yoga, 2023)
We are all aware of the medicinal properties of different plants mentioned in ayurveda. But in science there is always the exception. One such exception to the science of ayurveda is found in the seeds of Eleocarpus ganitrus whose seeds are commonly known as Rudraksh in India. The plant Eleocarpus ganitrus is known for its effectiveness in the treatment of various neurological ailments like sleeplessness, stress, anxiety, depression as well as for hypertension, rheumatism, asthma etc. Most of these neurological problems is caused by vata dosha imbalance which can be rectified by the Rudraksh seeds. Rudraksh seeds come in multi faced beads. In this review we would not only explore the medicinal properties of Eleocarpus ganirtus but would also explore the exceptional qualities of different multi faced Rudraksh beads used for treating specific diseases based on their number of faces.